Perancangan Dan Evaluasi Sistem Filtrasi Berbasis Bahan Alami Untuk Peningkatan Kualitas Air Bersih - Desilvi Ayu Tari Sasim; Tracey Precilia Mirino; Arbiatun, Fatimah (Casuarina: Jurnal Teknik Lingkungan, 2024)
This study examines the effectiveness of a simple water filtration system using a combination of natural media and coagulants. The filter system comprises coconut fiber, coastal sand, zeolite, activated carbon, wood charcoal, gravel, and coral fragments. Alum and Moringa seeds were tested as coagulants. The filtration process demonstrated a reduction in turbidity from >1000 NTU to 6.94 NTU and pH normalization from 8.3 to 6.9. However, increases in TDS and conductivity were observed. Post-filtration coagulant application yielded varied results, with Moringa seeds showing greater potential in maintaining pH and water clarity compared to alum. Although some parameters such as pH, TDS, and temperature met clean water standards after treatment, high TSS (>1000 mg/L) and turbidity (72.5-270 NTU) levels indicate the need for further optimization. This research highlights both the potential and challenges in developing water treatment systems based on local resources, as well as the importance of adjusting settling time and coagulant dosage to enhance the quality of treated water.